Pay trends in 2016 and outlook for 2017: a TUC report (London, 2017)
""Pay Trends in 2016 and Outlook for 2017” is a new report for the TUC from Incomes Data Research setting out the state of pay in the UK. The report first analyses hundreds of 2016 settlements by sector before discussing the prospects for 2017. Key themes for this year include inflation, public sector pay, and Brexit. A must-read for trade union negotiators, stewards and anyone who want to understand the current context of pay bargaining. "